Applying ADDIE Model to Evaluate faculty Development Programme - Bamrara, Atul (JOURNAL OF INDIAN EDUCATION, 2017)
We exist in a technology era where everything is controlled via electronic devices and education is also highly impacted from ICT (information and communication technology) tools. The present study is an attempt to highlight the training need analysis approach and its applicability. Further, it focuses on the application of ICT tools to analyse the data patterns during training need. ADDIE approach has been chosen to explore the correlation between techniques/approaches of training need analysis and evaluation of training programme.